2017
DOI: 10.1111/cch.12493
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐child interactions and children with cerebral palsy: An exploratory study investigating emotional availability, functional ability, and parent distress

Abstract: Findings from this study are consistent with the wider literature showing a link between parental depression and the parent-child relationship and extend this link to the cerebral palsy population. The importance of routine screening for parental mental health problems in early childhood intervention is highlighted by these findings. In addition, this study emphasizes the need to better understand how therapists support parents to implement therapeutic strategies to minimize negative impact on the developing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
3
21
0
5
Order By: Relevance
“…In a study that used the same child-reported parenting dimensions, Cohen et al (2008) found that rejecting parenting positively predicted an external locus of control (i.e., the perception of not being able to control one's life) in children and adolescents with CP. A third relevant study found that parents' responsiveness, as observed during interactions with their child (aged between 2 and 12 years), related negatively to child behavioral problems and positively to prosocial child behavior (Barfoot et al, 2017). Further, research showed that childperceived overprotection (i.e., an autonomy-suppressing type of parenting involving excessive protection) related to more anxiety and less happiness (Ho et al, 2008) and to lower self-esteem (Manuel, Balkrishnan, Camacho, Smith, & Koman, 2003) in children, adolescents, and early adults with CP.…”
Section: The Influence Of Parenting On the Development Of Children Wimentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that used the same child-reported parenting dimensions, Cohen et al (2008) found that rejecting parenting positively predicted an external locus of control (i.e., the perception of not being able to control one's life) in children and adolescents with CP. A third relevant study found that parents' responsiveness, as observed during interactions with their child (aged between 2 and 12 years), related negatively to child behavioral problems and positively to prosocial child behavior (Barfoot et al, 2017). Further, research showed that childperceived overprotection (i.e., an autonomy-suppressing type of parenting involving excessive protection) related to more anxiety and less happiness (Ho et al, 2008) and to lower self-esteem (Manuel, Balkrishnan, Camacho, Smith, & Koman, 2003) in children, adolescents, and early adults with CP.…”
Section: The Influence Of Parenting On the Development Of Children Wimentioning
confidence: 99%
“…This pathway indicates that daily feelings of pressure, social alienation, and personal failure leave parents vulnerable to relying on pressuring behaviors when interacting with their child. The need-frustrating experiences probably cause feelings of stress and agitation among parents, feelings that, in turn, prompt parents to engage in more dysfunctional parenting behaviors (Barfoot et al, 2017;Dieleman et al, 2018, Van der Kaap-Deeder et al, 2019.…”
Section: Parents' Daily Psychological Needs In Relation To Daily Parementioning
confidence: 99%
“…There were links between parent distress and lower levels of emotional availability for parents and their child with CP. In contrast to expectations, Barfood et al [21] found no association between emotional availability and the level of the child's functional status. Results do not always converge, probably as a consequence of the samples' heterogeneity and the methodologies employed in the different studies.…”
Section: Discussionmentioning
confidence: 83%
“…There were conflicting results. Some studies found that depression and anxiety levels of mothers were associated with functional disability levels in children with CP [18,19] and others were not found any assosiation beetween mothers mood and functional level of children with CP [20,21]. There were links between parent distress and lower levels of emotional availability for parents and their child with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Many physical, occupational, and speech and language therapy interventions, however, focus on improving (motor) performance of the child, which often requires a task-oriented approach [4]. Hence, implementation of therapeutic strategies can interfere with the parent-child emotional availability and interaction [6,9]. These potential disadvantageous consequences of collaborative service delivery can lead to an increase of perceived parental stress as a secondary, adverse effect of paramedical therapies (i.e., physical, occupational, and speech and language therapy) [7].…”
Section: Introductionmentioning
confidence: 99%